4.0k views
4 votes
How do I solve for m?

How do I solve for m?-example-1
User Jemiloii
by
5.2k points

2 Answers

2 votes


x^3y^2\left((x^2 y^3 z^m)/(z^(-5))\right)=x^5y^5z\\\\ x^5y^5z^(m+5)=x^5y^5z\\\\ m+5=1\\\\ \boxed{m=-4}

User Roki
by
5.2k points
4 votes

Step One

Bring z^(-5) to the numerator.

x^3y^2(x^2 y^3 z^(m + 5)) = x^5 * 5y^5 * z

Step Two

Remove the brackets on the left

x^(3 + 2) * y ^ (2 + 3) * z^(m + 5) = x^5 * y^5 * z

x^5 * y^5 * z^(m + 5) = x^5 * y^5 * z Divide by x^5 * y^5

z ^(m + 5) = z^1 Since the bases are the same, you can equate the powers.

m + 5 = 1 Subtract 5

m = 1 - 5

m = - 4 <<<< Answer


User Spartak
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.